Estrogen Contributions to Microvascular Dysfunction Evolving to Heart Failure With Preserved Ejection Fraction - Sickinghe, Ariane A.; Korporaal, Suzanne J. A.; den Ruijter, Hester M.; Kessler, Elise L. (Frontiers in Endocrinology, 2019)
Heart failure with preserved ejection fraction (HFpEF) is a syndrome involving microvascular dysfunction. No treatment is available yet and as the HFpEF patient group is expanding due to the ageing population, more knowledge on dysfunction of the cardiac microvasculature is required. Endothelial dysfunction, impaired angiogenesis, (perivascular) fibrosis and the pruning of capillaries (rarefaction) may all contribute to microvascular dysfunction in the heart and other organs, e.g. the kidneys. The HFpEF patient group consists mainly of post-menopausal women and female sex itself is a risk factor for this syndrome. This may point towards a role of estrogen depletion after menopause in the development of HFpEF. Estrogens favor the ratio of vasodilating over vasoconstricting factors, which results in an overall lower blood pressure in women than in men. Furthermore, estrogens improve angiogenic capacity and attenuate (perivascular) fibrosis formation. Therefore, we hypothesize that the drop of estrogen levels after menopause contributes to myocardial microvascular dysfunction and renders post-menopausal women more vulnerable for heart diseases that involve the microvasculature. This review provides a detailed summary of molecular targets of estrogen, which might guide future research and treatment options.